Measuring the effective levels of company taxation in the New Member States a quantitative analysis - Finkenzeller, Martin; Spengel, Christoph 1964- (Office for Official Publ. of the Europ. Communities, 2004)
Recoge: 1.Introduction - 2.Methodology and theorical framework - 3.Corporate taxation in the new member states - 4.Effective tax burdens on domestic investments in the new member states - 5.Effective tax burdens on german outbound investments to the new member states.
Keywords: Europäische Union; European Union; Belastingen; Europese Unie; Uitbreidingen; Multinationales Unternehmen; Steuer; Corporations -- Taxation -- European Union countries; International business enterprises -- Taxation -- European Union countries; Europäische Union. Mitgliedsstaaten